Anti‐pruritic effect of isothiocyanates: Potential involvement of toll‐like receptor 3 signaling - Masaki Moriyama; Mitsuhiro Konno; Kanako Serizawa; Natsumi Yuzawa; Yuki Majima; Ikuo Hayashi; Tomohiko Suzuki; Mie Kainoh (Wiley, 2022)
Abstract The innate immune system has an emerging role as a mediator of neuro‐immune communication and a therapeutic target for itch. Toll‐like receptor 3 (TLR3) plays an important role in itch, as shown in TLR3 knock‐out mice. In this study, to evaluate effects of TLR3 inhibitors on histamine‐independent itch, we used two kinds of isothiocyanate (ITC). Both phenethyl isothiocyanate (PEITC) and sulforaphane (SFN) inhibited Poly I:C (PIC)‐induced signaling in the RAW264.7 cell line. We then investigated the anti‐pruritic effect of these compounds on PIC‐ and chloroquine (CQ)‐induced scratching behavior. PEITC and SFN both suppressed PIC‐evoked scratching behavior in mice, and PEITC also inhibited CQ‐induced acute itch. Finally, we examined the oxazolone‐induced chronic itch model in mice. Surprisingly, oral dosing of both compounds suppressed scratching behaviors that were observed in mice. Our findings demonstrate that TLR3 is a critical mediator in acute and chronic itch transduction in mice and may be a promising therapeutic target for pruritus in human skin disorders. It is noteworthy that SFN has potential for use as an antipruritic as it is a phytochemical that is used as a supplement.